Zinc-plated steel sheet and method for producing same
By forming a specific composition organic resin film on the surface of the zinc-based plated steel plate, the problem of large sliding resistance during stamping is solved, excellent stamping forming and welding properties are achieved, and the smooth progress of the coating process is ensured.
Patent Information
- Application Number
- CN202380054437.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-26
- Filing Date
- 2023-06-14
- Publication Date
- 2025-02-21
AI Technical Summary
The zinc-based plated steel plate has a large sliding resistance during stamping, resulting in poor forming properties and prone to steel plate breakage. The prior art relies on high viscosity lubricating oil or mold surface treatment, which has problems such as coating defects and high cost.
The organic resin film is formed on the surface of the zinc-based plated steel plate, and specifically a coating containing acrylic resin and polyolefin wax is used. The glass transition temperature of the acrylic resin is 100°C or more, and the ratio of the acid value to the glass transition temperature is 1.50 As above, the melting point of the wax is 100°C or higher and 145°C or lower, the average particle size is 3.0 μm or lower, the proportion of the wax is 5 mass % or higher, and the adhesion amount of the film is 0.2 g/m2 or higher and 2.5 g/m2 or lower.
The friction coefficient between the zinc-based plated steel plate and the mold is significantly reduced, stamping forming properties are improved, and the stability of complex forming is ensured. The welding, film removal and adhesiveness are also excellent, avoiding interference from the coating process.
Smart Images

Figure CN119497763A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a zinc-plated steel sheet having excellent sliding properties during press forming and a method for producing the same, and more particularly to a zinc-plated steel sheet having a lubricating film and excellent formability even during severe drawing and a method for producing the same. Background Art
[0002] Zinc-plated steel sheets are widely used in a wide range of fields, centered around automobile body applications. In such applications, they are usually used after being subjected to stamping. However, compared to cold-rolled steel sheets, zinc-plated steel sheets have the disadvantage of poor stamping formability. The reason for this is that the sliding resistance of zinc-plated steel sheets in the stamping die is greater than that of cold-rolled steel sheets. That is, during deep drawing, zinc-plated steel sheets with large sliding resistance with the blank holder are not easy to flow into the stamping die side, and the steel sheets are prone to breakage. When the sliding resistance with the die is large during bulging and embossing, strain localization occurs, and the steel sheets are also prone to breakage.
[0003] Therefore, as a method for improving the stamping formability of zinc-plated steel sheets during use, a method of applying a high-viscosity lubricating oil is widely used. However, in this method, the lubricating oil is highly viscous, so coating defects caused by poor degreasing sometimes occur in the coating process. In addition, there are problems such as the stamping performance becoming unstable due to oil cutoff during stamping. In addition, as another method for improving the stamping formability, surface treatment of the mold can be listed. Surface treatment of the mold is a widely used method, but in this method, the mold cannot be adjusted after the surface treatment is implemented. In addition, there is a problem of high cost. Therefore, it is required to improve the stamping formability of the zinc-plated steel sheet itself that does not rely on high-viscosity lubricating oil and surface treatment of the mold.
[0004] Therefore, various lubricating surface-treated steel sheets have been studied as a means of solving the above-mentioned problems.
[0005] Patent Document 1 describes a technique for forming a lubricating film containing synthetic resin powder in an acrylic resin film on a zinc-plated steel sheet.
[0006] Patent Document 2 describes a metal plate coated with a lubricating film in which a solid lubricant protrudes from the surface of a resin film by 0.01 to 1.5 μm.
[0007] Patent Document 3 describes a lubricated surface-treated metal product having excellent press formability and coated with a film having a thickness of 0.5 to 5 μm and made by adding a lubricant to a polyurethane resin.
[0008] Patent Document 4 describes a technique for forming an alkali-soluble organic film obtained by adding a lubricant to an epoxy resin on a steel plate.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 9-170059
[0012] Patent Document 2: Japanese Patent Application Laid-Open No. 10-52881
[0013] Patent Document 3: Japanese Patent Application Publication No. 2000-309747
[0014] Patent Document 4: Japanese Patent Application Publication No. 2000-167981 Summary of the invention
[0015] Problems to be solved by the invention
[0016] However, in Patent Documents 1 to 4, although lubricity is exhibited by the lubricating effect of the contained lubricant and the like, press formability is not necessarily sufficient for complex forming.
[0017] The present invention is completed in view of the above situation, and its purpose is to provide a zinc-plated steel sheet and a manufacturing method thereof, wherein the zinc-plated steel sheet is a zinc-plated steel sheet that is difficult to stamp, has low sliding resistance during stamping, and has excellent stamping formability.
[0018] In addition, when zinc-plated steel sheets are used as automobile bodies, they need to have excellent adhesion and weldability in the assembly process, and also need to have sufficient releasability in the alkali degreasing process in the painting process.
[0019] Here, zinc-plated steel sheet refers to a steel sheet on which a coating film mainly composed of zinc is formed. Examples of the coating film mainly composed of zinc include a zinc plating layer composed of zinc and unavoidable impurities without intentionally adding components other than zinc; a zinc plating layer mainly composed of zinc and added with alloy elements such as iron, nickel, aluminum, magnesium, and compounds such as aluminum oxide and silicon dioxide. The adhesion amount of the zinc plating of the zinc-plated steel sheet is not particularly limited, and it is preferably 3 to 120 g / m per single side. 2 .
[0020] Methods used to solve problems
[0021] The inventors of the present invention have conducted intensive research to solve the above problems. As a result, they found that by applying a coating weight W of 0.2 g / m2 on the surface of a zinc-coated steel sheet, 2 Above and 2.5g / m 2The above-mentioned problem can be solved by forming an organic resin film in the following range, wherein the organic resin film contains: an acrylic resin having a glass transition temperature (Tg) of 100°C or higher and an acid value ratio R = acid value (mg-KOH / g) / Tg (°C) of 1.50 or higher; and 5% by mass or more of a polyolefin wax having a melting point of 100°C or higher and 145°C or lower and an average particle size of 3.0 μm or lower.
[0022] The present invention has been accomplished based on the above findings, and the gist of the present invention is as follows.
[0023] [1] A zinc-plated steel sheet having a coating containing an acrylic resin and a wax formed on at least one surface thereof, wherein the acrylic resin has a glass transition temperature (Tg) of 100°C or higher, a ratio of acid value to glass transition temperature (R = acid value (mg-KOH / g) / Tg (°C) of 1.50 or higher, the wax is a polyolefin wax having a melting point of 100°C or higher and 145°C or lower and an average particle size of 3.0 μm or lower, the proportion of the wax in the coating is 5% by mass or higher, and the coating has an adhesion weight W per single surface of 0.2 g / m 2 Above and 2.5g / m 2 the following.
[0024] [2] The zinc-plated steel sheet according to [1], wherein the acid value of the acrylic resin is 180 mg-KOH / g or more and 350 mg-KOH / g or less.
[0025] [3] The zinc-plated steel sheet according to [1] or [2], wherein the ratio R of the acid value to the glass transition temperature of the acrylic resin is 2.05 or less.
[0026] [4] The zinc-plated steel sheet according to any one of [1] to [3], wherein the film contains 30% by mass or more of the acrylic resin, and the proportion of the wax is 50% by mass or less.
[0027] [5] The zinc-plated steel sheet according to any one of [1] to [4], wherein the mass average molecular weight of the acrylic resin is 5,000 or more and 30,000 or less.
[0028] [6] The zinc-plated steel sheet according to any one of [1] to [5], wherein the acrylic resin is a styrene acrylic resin.
[0029] [7] The zinc-plated steel sheet according to any one of [1] to [6], wherein the arithmetic mean roughness Ra of the surface of the zinc-plated steel sheet before the film is formed is 0.4 μm or more and 2.5 μm or less.
[0030] [8] The zinc-plated steel sheet according to any one of [1] to [7], wherein the film contains 1 mass % or more and 30 mass % or less of a rust inhibitor.
[0031] [9] The zinc-plated steel sheet according to [8], wherein the rust inhibitor is at least one selected from the group consisting of aluminum salts, zinc salts of phosphoric acid, and zinc oxide.
[0032]
[10] The zinc-plated steel sheet according to any one of [1] to [9], wherein the average particle size of the wax is 0.01 μm or more and 0.5 μm or less.
[0033]
[11] The zinc-plated steel sheet according to any one of [1] to
[10] , wherein the film contains 1 mass % or more and 10 mass % or less of silicon dioxide.
[0034]
[12] A method for manufacturing a zinc-plated steel sheet, which is the method for manufacturing a zinc-plated steel sheet described in any one of [1] to
[11] , wherein a coating containing an acrylic resin and a wax described in any one of [1] to
[11] is applied to at least one surface of the zinc-plated steel sheet and dried.
[0035]
[13] The method for producing a zinc-coated steel sheet according to
[12] , wherein the maximum reaching temperature of the zinc-coated steel sheet during the drying is 60° C. or higher and below the melting point of the wax.
[0036]
[14] The method for producing a zinc-coated steel sheet according to
[12] or
[13] , wherein the ratio of the total solid content in the coating material is 1% by mass or more and 30% by mass or less.
[0037] Effects of the Invention
[0038] According to the present invention, a zinc-plated steel sheet having a significantly reduced friction coefficient with a die and excellent stamping formability can be obtained. Therefore, the zinc-plated steel sheet having a complex forming process has stable excellent stamping formability. In addition, the weldability is also excellent.
[0039] In addition, since the zinc-plated steel sheet with a suitable coating has good adhesiveness and releasability, the adhesive can be used in the same way as the conventional zinc-plated steel sheet, and the releasability by alkali degreasing is excellent, so the painting process is not hindered. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a schematic front view showing a friction coefficient measuring device.
[0041] Figure 2 It is shown Figure 1 Schematic diagram of the shape and size of the binder rib. DETAILED DESCRIPTION
[0042] Hereinafter, embodiments of the present invention will be described.
[0043] The zinc-plated steel sheet of the present invention is a zinc-plated steel sheet having a coating containing an acrylic resin and a wax formed on at least one side, wherein the glass transition temperature (Tg) of the acrylic resin is 100°C or higher, the ratio of the acid value to the glass transition temperature R = acid value (mg-KOH / g) / Tg (°C) is 1.50 or higher, the wax is a polyolefin wax having a melting point of 100°C or higher and 145°C or lower and an average particle size of 3.0 μm or lower, the proportion of the wax in the coating is 5% by mass or higher, and the adhesion amount W of the coating per single side is 0.2 g / m 2 Above and 2.5g / m 2 the following.
[0044] Hereinafter, the ratio of the acid value to the glass transition temperature R=acid value (mg-KOH / g) / Tg (° C.) is expressed as R=acid value / Tg.
[0045] The glass transition temperature of the acrylic resin of the film of the present invention is set to 100°C or more in order to obtain good lubricity. When the glass transition temperature is lower than 100°C, the resin softens during sliding, the holding power of the wax decreases, and the ability to prevent direct contact between the zinc-plated steel sheet and the mold decreases, so good sliding properties cannot be obtained. The glass transition temperature is preferably 110°C or more and 150°C or less. When the glass transition temperature exceeds 150°C, on the contrary, the hardness of the resin tends to become high and brittle during sliding, and excellent lubricity cannot be obtained.
[0046] Here, the glass transition temperature refers to an intermediate glass transition temperature measured in accordance with JIS K 7121 "Methods for determining transition temperatures of plastics".
[0047] The ratio of the acid value to the glass transition temperature of the acrylic resin, R = acid value / Tg, is set to 1.50 or more. Even if the glass transition temperature is 100°C or more, excellent lubricity cannot be obtained when the acid value is low (R < 1.50). Although the reason is not clear, it is believed that the carboxyl group in the acrylic resin has a high affinity with the mold, and the effect of transferring the polyolefin wax in the film to the mold during sliding is obtained. By transferring the acrylic resin component containing polyolefin wax to the mold during sliding, the mold surface is protected by the polyolefin wax, and the effect of preventing direct contact with the zinc-plated steel sheet is improved, and the sliding property is improved. Therefore, in the case of a low acid value (R < 1.50), the carboxyl group is insufficient, and the sliding property is poor. When the glass transition temperature of the acrylic resin is increased, it is difficult to soften the resin by sliding, and therefore it is difficult to transfer to the mold. Therefore, in order to obtain excellent sliding properties when the glass transition temperature is increased, the acid value needs to be increased. That is, the ratio of the acid value to the glass transition temperature, R = acid value / Tg, needs to be set to 1.50 or more. R is preferably 1.80 or more. It should be noted that the upper limit of R is not particularly limited, but is preferably set to 2.05 or less. This is because when R exceeds 2.05, the rust prevention property may deteriorate.
[0048] In addition, the acid value of the acrylic resin is preferably 180 mg-KOH / g or more and 350 mg-KOH / g or less. When it is less than 180 mg-KOH / g, the demolding property by alkali may be poor, and the bonding strength by the adhesive may not be sufficiently obtained. When it exceeds 350 mg-KOH / g, the rust resistance may be deteriorated.
[0049] Here, the acid value refers to the number of mg of potassium hydroxide required to neutralize the carboxyl groups contained in 1 g of the resin, and is measured based on JIS K0070 "Test methods for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemicals". In the present invention, the unit is expressed in mg-KOH / g.
[0050] The wax used in the present invention may be any polyolefin wax having a melting point of 100° C. to 145° C. and an average particle size of 3.0 μm or less.
[0051] Polyolefin wax is used as the wax because it has low surface energy and self-lubricating properties, thus providing good lubricity. In addition, polyolefins can be easily adjusted to have a melting point of 100° C. or higher and 145° C. or lower by controlling density and molecular weight.
[0052] When the melting point of the polyolefin wax is above 100°C and below 145°C, in addition to the self-lubricating property of the polyolefin wax itself, the sliding during stamping makes the polyolefin wax semi-molten, so that the lubricating film component mixed with the acrylic resin can cover the mold surface. Thus, by suppressing the direct contact between the mold and the zinc-plated steel sheet, an excellent lubrication effect can be obtained. When the melting point of the polyolefin wax is lower than 100°C, it is completely melted due to the frictional heat caused by the sliding during stamping, and the sufficient lubrication effect of the polyolefin wax itself cannot be obtained, and the coating effect of the above-mentioned mold cannot be obtained. In addition, when the melting point of the polyolefin wax exceeds 145°C, the polyolefin wax does not melt during sliding, and the sufficient lubrication effect cannot be obtained, and the coating effect of the mold cannot be obtained. Furthermore, the melting point of the polyolefin wax is preferably above 120°C and below 140°C.
[0053] Here, the melting point of the polyolefin wax refers to the melting temperature measured based on JIS K 7121 "Determination of Transition Temperatures of Plastics".
[0054] When the average particle size of the polyolefin wax exceeds 3.0 μm, it is difficult to mix with the acrylic resin during sliding, and the mold coating effect and sufficient lubricity cannot be obtained. The average particle size of the polyolefin wax is preferably 0.5 μm or less, and more preferably 0.3 μm or less.
[0055] The average particle size of the polyolefin wax is preferably 0.01 μm or more. When the average particle size of the polyolefin wax is less than 0.01 μm, it is easy to dissolve in the lubricating oil during sliding, and sometimes it cannot fully exert the lubricity improvement effect. It is also easy to agglomerate in the coating used to form the film, so the coating stability is also low. The average particle size of the polyolefin wax is more preferably 0.03 μm or more. If the miscibility with the above-mentioned acrylic resin is also considered, the average particle size of the polyolefin wax is preferably 0.01 μm or more and 0.5 μm or less.
[0056] The average particle size is the median diameter of the volume average diameter, which is obtained by laser diffraction / scattering method, for example, by measuring a sample diluted with pure water using a laser diffraction / scattering particle size distribution measuring device Partica (registered trademark) LA-960V2 (manufactured by Horiba, Ltd.).
[0057] Among the polyolefin waxes, polyethylene wax is preferably used because the best lubricating effect can be obtained.
[0058] The mass ratio of the polyolefin wax in the film is set to 5% by mass or more. When the mass ratio of the polyolefin wax in the film is less than 5% by mass, sufficient lubrication effect cannot be obtained. If the mass ratio of the polyolefin wax in the film is 10% by mass or more, a particularly good lubrication effect can be obtained. In addition, the mass ratio of the polyolefin wax in the film is preferably 50% by mass or less. When the mass ratio of the polyolefin wax in the film exceeds 50% by mass, sometimes the polyolefin wax is easy to fall off due to the deficiency of the matrix resin component, and the adhesion to the steel plate is poor, and it cannot be stably present as a film, and the adhesion is poor. In addition, when used as a car body, sometimes sufficient degreasing is not obtained in the alkali degreasing process in the coating process, and sometimes the film is not fully stripped in the alkali degreasing process, and the film remains, which deteriorates the coating property. The mass ratio of the polyolefin wax in the film is further preferably 30% by mass or less.
[0059] Here, the mass ratio of the polyolefin wax in the coating film refers to the ratio of the mass of the solid content of the polyolefin wax to the mass of the total solid content in the coating material.
[0060] The film of the present invention preferably contains 30% by mass or more of the acrylic resin. When the mass ratio of the acrylic resin in the film is 30% by mass or more, the properties affected by the physical properties of the acrylic resin component, such as the lubricity improvement effect brought about by the transfer to the mold during sliding, demolding properties, and adhesion, can be fully obtained. When the mass ratio of the acrylic resin in the film is less than 30% by mass, the influence of other components becomes large, and the target performance may not be obtained.
[0061] The mass average molecular weight of the acrylic resin is preferably 5000 to 30000. When the mass average molecular weight of the acrylic resin is less than 5000, the rust prevention may be poor, and when it exceeds 30000, the adhesiveness may be deteriorated.
[0062] Here, the mass average molecular weight means a mass average molecular weight measured in accordance with JIS K 7252 "Plastics - Method for determining average molecular weight and molecular weight distribution of polymers by size exclusion chromatography".
[0063] Furthermore, the acrylic resin is preferably a styrene acrylic resin. By containing styrene in the monomer of the resin, water resistance is improved, so the rust resistance is good. In addition, it is also found that the effect of obtaining good sliding properties compared with the case of not containing styrene.
[0064] The film of the present invention preferably contains a rust inhibitor of more than 1% by mass and less than 30% by mass in the film. Even if it does not contain a rust inhibitor, it will not rust or discolor under a normal storage environment, but when the content of the rust inhibitor is less than 1% by mass, it will sometimes rust under an unfavorable storage environment. In particular, when the steel strip is stored in a high humidity environment in a state where it is superimposed in a coil, it sometimes absorbs moisture and discolors. When the ratio of the rust inhibitor exceeds 30% by mass, the adhesion sometimes deteriorates, and in addition, the rust inhibitor sometimes precipitates in the state of the coating, and the coating stability deteriorates. As the rust inhibitor, it is preferred to use at least one selected from the group consisting of aluminum salts, zinc salts and zinc oxide of phosphoric acid. Here, phosphoric acid, in addition to orthophosphoric acid, also includes condensed phosphoric acids such as pyrophosphoric acid, tripolyphosphoric acid, tetrapolyphosphoric acid, and metaphosphoric acid. By using these rust inhibitors, a sufficient rust-proof effect can be exerted, and then the deterioration of the coating stability is also small.
[0065] In addition, the film of the present invention preferably contains 1% by mass or more and 10% by mass or less of silicon dioxide in the film. By containing silicon dioxide, the water repellency of the film is improved and the rust resistance is improved. In addition, by containing silicon dioxide, the precipitation of the rust inhibitor can be suppressed and the coating stability is improved. In addition, when the content is less than 1% by mass, it is difficult to obtain the above effect; when it exceeds 10% by mass, the adhesion is sometimes deteriorated. In the case of containing silicon dioxide in the film of the present invention, colloidal silicon dioxide with a particle size of 5nm or more and 200nm or less is preferably used.
[0066] In the present invention, as components other than the acrylic resin, wax, rust inhibitor, and silica, a surface conditioner, a defoaming agent, a dispersant, and the like, which are usually added to a coating material, may be included.
[0067] The surface roughness of the zinc-plated steel sheet used in the present invention before the film is formed is preferably 0.4 μm or more and 2.5 μm or less in terms of arithmetic mean roughness Ra. When Ra is 2.5 μm or less, the lubrication effect brought by the film can be stably obtained. When Ra is less than 0.4 μm, sometimes fine damage that may occur during stamping is easy to be conspicuous, and sometimes die sticking occurs during stamping. When Ra exceeds 2.5 μm, the unevenness of the steel sheet becomes larger, so sometimes the film in the concave part is difficult to function effectively during sliding, and the lubrication effect brought by the film is reduced. The arithmetic mean roughness Ra (μm) of the steel sheet can be measured in accordance with JIS B0633: 2001 (ISO 4288: 1996). For example, when Ra is greater than 0.1 and less than 2, the cutoff value and the reference length are set to 0.8 mm, and the evaluation length is set to 4 mm, and the roughness curve is measured. When Ra is more than 2 and not more than 10, the cutoff value and the reference length are set to 2.5 mm, and the evaluation length is set to 12.5 mm, and the roughness curve is obtained from the measurement.
[0068] The coating weight per single side of the zinc-plated steel sheet is 0.2 g / m2 in terms of dry weight. 2 Above and 2.5g / m 2 The following method is used to form the 2 When the lubricity is too high, sometimes sufficient sliding properties cannot be obtained; when the lubricity is more than 2.5 g / m 2 When the alkali-based weldability, mold release properties, and adhesiveness may deteriorate.
[0069] Next, the method for producing the zinc-based plated steel sheet of the present invention will be described.
[0070] The manufacturing method of the zinc-plated steel sheet of the present invention is a manufacturing method of the zinc-plated steel sheet with an acrylic resin coating as described below, wherein the steel sheet has a coating containing an acrylic resin and a wax formed on at least one surface, and the acrylic resin coating contains: an acrylic resin having a glass transition temperature (Tg) of 100°C or higher and a ratio of acid value to glass transition temperature R = acid value / Tg of 1.50 or higher; and 5% by mass or more of a polyolefin wax having a melting point of 100°C or higher and 145°C or lower and an average particle size of 3.0 μm or lower.
[0071] First, the manufacturing method of the zinc-coated steel sheet of the present invention is described. A zinc-coated steel sheet such as a cold-rolled steel sheet or a hot-rolled steel sheet is subjected to a zinc-coated treatment. The method of the zinc-coated treatment is not particularly limited, and for example, it can be formed by applying zinc-coated steel sheets to the steel sheets by various manufacturing methods such as hot-dip plating, electroplating, vapor deposition, and spraying. In addition, an alloyed hot-dip galvanized steel sheet subjected to an alloying treatment after the zinc-coated treatment can also be used. In addition, zinc-coated steel sheets containing metals other than zinc such as zinc-aluminum alloy plating, zinc-aluminum-magnesium alloy plating, and zinc-nickel alloy plating can also be implemented.
[0072] Next, the method for forming an acrylic resin film is described. An acrylic resin solution obtained by dissolving or dispersing an acrylic resin in a solvent or a coating having wax added to an emulsion is applied to at least one side of a zinc-plated steel sheet and dried. As a solvent for the coating, water or an organic solvent can be used, preferably water. The concentration of all solid components in the coating is preferably 1% by mass or more and 30% by mass or less. When the concentration of all solid components in the coating is less than 1% by mass or more than 30% by mass, uneven coating sometimes occurs. There is no particular limitation on the coating method, and examples thereof include methods using a roller coater or a rod coater, and coating methods using spraying, dipping, and brushing. The drying method of the coated steel sheet can be carried out by a general method. For example, drying using hot air, drying using an IH heater, and methods using infrared heating can be cited. The maximum reaching temperature of the zinc-plated steel sheet during drying is preferably above 60°C and below the melting point of the wax used. When the maximum reaching temperature of the zinc-plated steel sheet is lower than 60°C, drying takes time, and sometimes the rust resistance deteriorates. When the maximum reaching temperature of the zinc-plated steel sheet exceeds the melting point of the wax, the lubricity may be deteriorated due to the wax melting, coalescence, and coarsening. 2 Above and 2.5g / m 2 The coating adhesion amount can be obtained by dividing the weight difference of the zinc-plated steel sheet before and after the coating by the area, or by completely removing the coating of the zinc-plated steel sheet after the coating by an alkaline aqueous solution or an organic solvent having a pH of 10 to 13 and dividing the weight difference of the zinc-plated steel sheet before and after the coating is removed by the area.
[0073] Example
[0074] Hereinafter, the present invention will be described by way of examples. It should be noted that the present invention is not limited to the following examples.
[0075] Using alloyed hot-dip galvanized steel sheets (GA), electrogalvanized steel sheets (EG), and hot-dip galvanized steel sheets (GI) with a thickness of 0.8 mm and an arithmetic mean roughness Ra shown in Table 1, a coating of the composition shown in Table 2 was applied by a rod coater, and the steel sheets were dried by an IH heater in a manner such that the maximum reaching temperature of the steel sheets was 80°C, thereby preparing the zinc-plated steel sheets of the present invention as test materials. It should be noted that the steel sheets A to G are all zinc-plated steel sheets obtained by zinc-plating an SPCD (JIS G 3141) substrate having a tensile strength of 270 MPa. It should be noted that as silica, colloidal silica with a volume average particle size of 9 nm was used. In addition, the concentration of all solid components in the coating used was 3% to 25%.
[0076] The coating adhesion amount was determined by removing the coating of the zinc-plated steel sheet after coating with a sodium hydroxide aqueous solution at pH 12 and dividing the mass difference of the zinc-plated steel sheet before and after the coating removal by the area.
[0077]
[0078]
[0079] (1) Evaluation method of stamping formability (sliding characteristics)
[0080] In order to evaluate the press formability, the friction coefficient of each test material was measured as follows.
[0081] Figure 1 : is a schematic front view showing a friction coefficient measuring device. As shown in the figure, a friction coefficient measuring sample 1 cut from a test material is fixed to a sample table 2, and the sample table 2 is fixed to the upper surface of a horizontally movable sliding table 3. On the lower surface of the sliding table 3, there is a sliding table support seat 5 that can move up and down and has a roller 4 in contact with it. By pushing it up, a first load sensor 7 for measuring the pressing load N on the friction coefficient measuring sample 1 based on the blank holder 6 is installed on the sliding table support seat 5. The second load sensor 8 for measuring the sliding resistance F of the sliding table 3 moving in the horizontal direction under the above-mentioned pressing force is installed at one end of the sliding table 3. It should be noted that the surface of the sample 1 is coated with a stamping cleaning oil PRETON (registered trademark) R352L manufactured by SUGIMURA Chemical Industry Co., Ltd. as a lubricant for testing.
[0082] Figure 2 1 is a schematic perspective view showing the shape and size of the bead used. The bead 6 slides in a state where the lower surface of the bead is pressed against the surface of the sample 1 . Figure 2 The shape of the blank holder 6 shown is: the width is 10mm, the length in the sliding direction of the sample is 59mm, the lower part of the two ends in the sliding direction is composed of a curved surface with a curvature of 4.5mmR, and the lower surface of the blank holder that presses the sample has a plane with a width of 10mm and a length of 50mm in the sliding direction.
[0083] In the friction coefficient measurement test, the Figure 2 The blank holder shown in the figure was subjected to a pressing load N of 400 kgf and a sample pulling speed (horizontal moving speed of the slide table 3) of 20 cm / min. The friction coefficient μ between the test material and the blank holder was calculated by the formula: μ=F / N.
[0084] Regarding the evaluation of sliding properties, the case where the friction coefficient was 0.119 or less was evaluated as particularly excellent sliding properties and was evaluated as ◎, the case where the friction coefficient exceeded 0.119 and was 0.130 or less was evaluated as good sliding properties and was evaluated as 0, and the case where the friction coefficient exceeded 0.130 was evaluated as insufficient sliding properties.
[0085] (2) Evaluation method of weldability
[0086] For each test piece, a continuous spot welding test was conducted under the conditions of using a DR type Cr-Cu electrode, a pressing force of 150 kgf, a power-on time of 10 cycles / 60 Hz, and a welding current of 7.5 kA, and the evaluation was performed using the number of continuous spot welding. When the number of continuous spot welding was 90% or more compared to the zinc-plated steel sheet without an acrylic film, the weldability was evaluated as good and ○, and when it was less than 90%, the weldability was evaluated as insufficient and ×.
[0087] (3) Evaluation method of film release properties
[0088] Assuming that the steel plate of the present invention is used in automobile applications, the removability during degreasing is evaluated. In order to determine the removability of the film, each test piece is first degreased using FINE CLEANER (registered trademark) E6403 (manufactured by Japan Parkersei Co., Ltd.) as an alkaline degreasing agent. The degreasing treatment is performed by immersing the test piece in a degreasing solution with a degreasing agent concentration of 20 g / L and a temperature of 40°C for a prescribed period of time and then washing with tap water. The surface carbon intensity of the test piece after degreasing treatment is measured using a fluorescent X-ray analyzer, and the film peeling rate is calculated using the following formula using the measured value and the previously measured surface carbon intensity before degreasing and the measured value of the surface carbon intensity of the untreated metal plate.
[0089] Film peeling rate (%) = [(carbon strength before degreasing - carbon strength after degreasing) / (carbon strength before degreasing - carbon strength of untreated steel plate)] × 100
[0090] The film releasability was evaluated according to the following criteria based on the immersion time in the alkaline degreasing solution at which the film peeling rate reached 98% or more. The case of 120 seconds or less was evaluated as good releasability and 0, and the case of more than 120 seconds was evaluated as insufficient releasability and △.
[0091] (4) Evaluation method of rust resistance
[0092] Assuming that the zinc-plated steel sheet of the present invention is stored in the form of a coil as a steel strip, the rust resistance in the overlapped state was evaluated. Each test piece of the test material was processed into a size of 150 mm × 70 mm and the rust resistance was 1.0 g / m per single side. 2Anti-rust oil was applied on both sides, two test pieces were overlapped, and the contact pressure was 0.02kgf / mm 2 The test was conducted under a load of 50°C and a humidity of 95%RH. The rust resistance was evaluated by checking the inner surface of the overlapped film every 7 days and evaluating the number of days until discoloration occurred. The case of 56 days or more was evaluated as particularly good rust resistance and ◎, the case of 35 days or more was evaluated as good rust resistance and ○, and the case of less than 35 days was evaluated as insufficient rust resistance and △.
[0093] (5) Evaluation method of adhesion
[0094] Each test piece of the test material was processed into a size of 100×25.4mm, immersed in anti-rust oil and stood vertically for 24 hours to remove excess oil. Two test pieces obtained in this way were used, and epoxy adhesive was evenly applied to the 25.4mm×13mm part with a thickness of 0.2mm. Then, they were overlapped and clamped with clips, and sintered at 180°C for 20 minutes to dry and solidify. After cooling, a shear tensile test was performed using a universal testing machine to measure the shear adhesion. Regarding adhesion, an adhesion of 20MPa or more was evaluated as good adhesion and ○, and an adhesion of less than 20MPa was evaluated as insufficient adhesion and △.
[0095]
[0096]
[0097]
[0098] According to Table 3-1 to Table 3-3, the zinc-plated steel sheets of the examples of the present invention all have excellent stamping formability and weldability. In contrast, the zinc-plated steel sheets of the comparative examples that do not have the technical features of the present invention all have poor stamping formability. In addition, the zinc-plated steel sheets of the examples of the present invention can have good demolding properties, rust resistance, and adhesion by selecting an appropriate technical range.
[0099] Industrial Applicability
[0100] The zinc-coated steel sheet of the present invention has excellent sliding property and weldability during press forming. In addition, by selecting an appropriate technical range, it can have good demoulding property, rust resistance and adhesiveness, and because it has these excellent properties, it can be applied to a wide range of fields centered on automobile body applications.
[0101] Explanation of symbols
[0102] 1 Specimen for determination of friction coefficient
[0103] 2 Sample table
[0104] 3 Sliding table
[0105] 4 Rollers
[0106] 5 Sliding table support
[0107] 6. Edge rib
[0108] 7 First load sensor
[0109] 8 Second load sensor
[0110] 9 Tracks
Claims
1. A zinc-plated steel sheet having a coating film containing an acrylic resin and a wax formed on at least one surface thereof, wherein: The acrylic resin has a glass transition temperature (Tg) of 100°C or higher, a ratio of acid value to glass transition temperature (R = acid value (mg-KOH / g) / Tg (°C) of 1.50 or higher, the wax is a polyolefin wax having a melting point of 100°C or higher and 145°C or lower and an average particle size of 3.0 μm or lower, the proportion of the wax in the film is 5% by mass or higher, and the adhesion amount W per single side of the film is 0.2 g / m 2 Above and 2.5g / m 2 the following.
2. The zinc-coated steel sheet according to claim 1, wherein: The acid value of the acrylic resin is 180 mg-KOH / g or more and 350 mg-KOH / g or less.
3. The zinc-based plated steel sheet according to claim 1 or 2, wherein: The acrylic resin has a ratio R of an acid value to a glass transition temperature of 2.05 or less.
4. The zinc-based plated steel sheet according to any one of claims 1 to 3, wherein The film contains 30% by mass or more of the acrylic resin, and the proportion of the wax is 50% by mass or less.
5. The zinc-based plated steel sheet according to any one of claims 1 to 4, wherein The mass average molecular weight of the acrylic resin is 5,000 or more and 30,000 or less.
6. The zinc-based plated steel sheet according to any one of claims 1 to 5, wherein The acrylic resin is styrene acrylic resin.
7. The zinc-based plated steel sheet according to any one of claims 1 to 6, wherein The arithmetic mean roughness Ra of the surface of the zinc-based plated steel sheet before the film is formed is 0.4 μm or more and 2.5 μm or less.
8. The zinc-based plated steel sheet according to any one of claims 1 to 7, wherein The film contains 1 mass % or more and 30 mass % or less of a rust inhibitor.
9. The zinc-based plated steel sheet according to claim 8, wherein: The rust inhibitor is at least one selected from the group consisting of aluminum salts, zinc salts and zinc oxide of phosphoric acid.
10. The zinc-based plated steel sheet according to any one of claims 1 to 9, wherein The wax has an average particle size of 0.01 μm or more and 0.5 μm or less.
11. The zinc-based plated steel sheet according to any one of claims 1 to 10, wherein The film contains 1 mass % or more and 10 mass % or less of silicon dioxide.
12. A method for producing a zinc-coated steel sheet, which is the method for producing a zinc-coated steel sheet according to any one of claims 1 to 11, wherein: A coating material containing the acrylic resin according to any one of claims 1 to 11 and a wax is applied to at least one surface of a zinc-plated steel sheet and dried.
13. The method for producing a zinc-based plated steel sheet according to claim 12, wherein: The maximum reaching temperature of the zinc-based plated steel sheet during the drying is 60° C. or higher and below the melting point of the wax.
14. The method for producing a zinc-based plated steel sheet according to claim 12 or 13, wherein: The ratio of the total solid content in the coating material is 1 mass % or more and 30 mass % or less.
Citation Information
Patent Citations
Galvanized steel sheet covered with alkali-soluble resin coating film having excellent adhesiveness by adhesive
JP1997170059A
Resin coated metal plate with mold drag resistance and corrosion resistance and its manufacture
JP1998052881A
Alkali-soluble type organic film-coated steel sheet having excellent adhesiveness and anti-mold galling property
JP2000167981A
Coating composition having ability to form lubricative film excellent in press-moldability and scuffing- resistance, and of alkali-soluble type, and metal product having lubricatively treated surface using this composition
JP2000309747A